2014
DOI: 10.1177/1060028014555540
|View full text |Cite
|
Sign up to set email alerts
|

Severe Romiplostim-Induced Rebound Thrombocytopenia After Splenectomy for Refractory ITP

Abstract: Physicians using romiplostim as a bridge to splenectomy should be cautious about withholding a scheduled dose around the time of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Uwagawa et al describe a case using eltrombopag to augment platelet counts prior to splenectomy [16]. Another case report describes recurrent thrombocytopenia after splenectomy after romiplostim dose was held in preparation for surgery; however, platelet count recovered once romiplostim was restarted [17]. As such, there may be a role for TPO-RAs in certain circumstances before splenectomy to increase platelet count to a safe surgical threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Uwagawa et al describe a case using eltrombopag to augment platelet counts prior to splenectomy [16]. Another case report describes recurrent thrombocytopenia after splenectomy after romiplostim dose was held in preparation for surgery; however, platelet count recovered once romiplostim was restarted [17]. As such, there may be a role for TPO-RAs in certain circumstances before splenectomy to increase platelet count to a safe surgical threshold.…”
Section: Discussionmentioning
confidence: 99%
“…12 Two patients required rescue therapy and platelet counts returned to baseline within three to seven days. Choe et al 10 reported a case of severe rebound thrombocytopenia after temporary discontinuation of romiplostim. The patient's platelet count of 434,000/mL necessitated that romiplostim dose be held according to prescribing information.…”
Section: Discussionmentioning
confidence: 99%
“…Choe et al. 10 reported a case of severe rebound thrombocytopenia after temporary discontinuation of romiplostim. The patient’s platelet count of 434,000/µL necessitated that romiplostim dose be held according to prescribing information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that romiplostim may be discontinued in select patients, even though there are concerns of a profound rebound thrombocytopenia following its discontinuation. 33 35 This is not a trivial question. Current wholesale price of romiplostim is $1,062.50 for a single-use vial of 250 µg or $2,125.00 for a single-use vial of 500 µg.…”
Section: Discussionmentioning
confidence: 99%